PERCENT FAT MASS AND BODY MASS INDEX AS CARDIORESPIRATORY FITNESS PREDICTORS IN YOUNG ADULTS - Dewi, Mira; Kustiyah, Lilik; Kuswari, Mury (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2015)
ABSTRACTThe present study aimed to analyze the association between body fatness measures, i.e. body mass index (BMI) and percent fat mass (% FM) with cardiorespiratory fitness (CRF) in young adults. Seventy five undergraduate students aged 19-21 years were included in this cross sectional study. Body composition was assessed by tetra polar Bioelectrical Impedance Analysis method, and CRF was determined as VO2 max level by conducting Balke test and flexibility by sit-and-reach test. Regression tests were performed to assess the associations between the body fatness measures and CRF. The mean (SD) % FM and BMI were 25.6 (8.3) % and 22.4 (4.2) kg/m2, respectively. Both BMI and % FM were inversely associated with VO2 max and flexibility. The associations of % FM with each CRF measure were stronger (% FM-VO2 max: R2=0.45, p<0.0001; % FM-flexibility: R2=0.16, p<0.0001) than those of BMI (BMI-VO2 max: R2= 0.12, p=0.002; BMI-flexibility: R2=0.07, p<0.0001). Including gender as a variable predictor greatly improved almost all associations. We suggest that %FM is a better predictor for VO2max than BMI. Further studies are needed to elucidate the relationships of body fatness measures adjusted for potential confounding factors with CRF measures other than VO2 max.Keywords: body mass index, cardiorespiratory fitness, percent fat massABSTRAKPenelitian ini bertujuan untuk menentukan hubungan antara persentase lemak tubuh (PLT) dan indeks massa tubuh (IMT) dengan kebugaran kardiorespiratorik (KKR) pada dewasa muda. Penelitian menggunakan desain potong lintang dengan melibatkan 75 orang mahasiswa usia 19-21 tahun. PLT ditentukan dengan metode tetra polar Bioelectrical Impedance dan KKR ditentukan dengan VO2max berdasarkan uji Balke dan fleksibilitas dengan uji sit-and-reach. Hubungan antara PLT dan IMT dengan KKR dianalisis dengan uji regresi. Rata-rata (standar deviasi) dari PLT dan IMT berturut-turut adalah 25,6 (8,3)% dan 22,4 (4,2) kg/m2. Baik PLT maupun IMT berbanding terbalik dengan nilai VO2 max dan fleksibilitas. Korelasi antara PLT dengan kedua komponen KKR lebih kuat (PLT-VO2 max: R2=0,45 p<0,0001; PLT-fleksibilitas: R2=0,16 p<0,0001) dibanding IMT (IMT-VO2 max: R2=0,12 p=0,002; IMT-fleksibilitas: R2=0,07 p<0,0001). Memasukkan gender sebagai prediktor variabel memperkuat semua korelasi kecuali antara PLT dan fleksibilitas. Diperlukan studi lebih lanjut untuk mempelajari hubungan antara komposisi tubuh termasuk faktor perancu potensial dengan fleksibilitas dan komponen KKR lainnya.Kata kunci: indeks massa tubuh, kebugaran kardiorespiratorik, persen lemak tubuh